Association Between Changes in Postoperative Opioid Utilization and Long-Term Health Care Spending Among Surgical Patients With Chronic Opioid Utilization. (March 2022) - Sun, Eric C.; Rishel, Chris A.; Jena, Anupam B.
Abstract : BACKGROUND: There is growing interest in identifying and developing interventions aimed at reducing the risk of increased, long-term opioid use among surgical patients. While understanding how these interventions impact health care spending has important policy implications and may facilitate the widespread adoption of these interventions, the extent to which they may impact health care spending among surgical patients who utilize opioids chronically is unknown. METHODS: This study was a retrospective analysis of administrative health care claims data for privately insured patients. We identified 53, 847 patients undergoing 1 of 10 procedures between January 1, 2004, and September 30, 2018 (total knee arthroplasty, total hip arthroplasty, laparoscopic cholecystectomy, open cholecystectomy, laparoscopic appendectomy, open appendectomy, cesarean delivery, functional endoscopic sinus surgery, transurethral resection of the prostate, or simple mastectomy) who had chronic opioid utilization (≥10 prescriptions or ≥120-day supply in the year before surgery). Patients were classified into 3 groups based on differences in opioid utilization, measured in average daily oral morphine milligram equivalents (MMEs), between the first postoperative year and the year before surgery: "stable" (<20% change), "increasing" (≥20% increase), or "decreasing" (≥20% decrease). We then examined the association between these 3 groups and health care spending during the first postoperative year, using a multivariable regression to adjust for observable confounders, such as patient demographics, medical comorbidities, and preoperative health care utilization. RESULTS: The average age of the sample was 62.0 (standard deviation [SD] 13.1) years, and there were 35, 715 (66.3%) women. Based on the change in average daily MME between the first postoperative year and the year before surgery, 16, 961 (31.5%) patients were classified as "stable, " 15, 463 (28.7%) were classified as "increasing, " and 21, 423 (39.8%) patients were classified as "decreasing." After adjusting for potential confounders, "increasing" patients had higher health care spending ($37, 437) than "stable" patients ($31, 061), a difference that was statistically significant ($6377; 95% confidence interval [CI], $5669–$7084; P < .001), while "decreasing" patients had lower health care spending ($29, 990), a difference (–$1070) that was also statistically significant (95% CI, –$1679 to –$462; P = .001). These results were generally consistent across an array of subgroup and sensitivity analyses. CONCLUSIONS: Among patients with chronic opioid utilization before surgery, subsequent increases in opioid utilization during the first postoperative year were associated with increased health care spending during that timeframe, while subsequent decreases in opioid utilization were associated with decreased health care spending.